A comparative study of venipuncture skills among intern students with and without simulator practice - Saima Rahman Shokhi; Alamgir Mahfuj Abir; Md Masud Parvej; Md Khademul Islam; Md Mahfuzul Haque (Research in Agriculture Livestock and Fisheries, 2024)
Blood collection from small animals is difficult due to the increased risk of problems involved in getting a blood sample. The purpose of this paper was to analyze skill training using a simulator in the venipuncture method and investigate its impact. Twenty Intern Veterinary students were randomly chosen from Sylhet Agricultural University's 23-batch DVM program. They were separated into two groups. One group (n=10) was exposed to a simulator before practicing on a live animal, while another (n=10) was not exposed to the simulator. They worked with a live animal. Students in the experimental group demonstrated a 50% skill efficacy. The control group demonstrated inferior skill, with 25% efficacy. The difference between groups was statistically significant (p<0.05). The experiment was carried out using a simple methodology and easily accessible resources to benefit other educational institutions and lessen the negative impact on live animals. Understanding the anatomy, physiology, and behavior of the species from whom the sample is being collected is critical for minimizing the risk of injury associated with venipuncture in these species. A physician must be aware of the benefits and drawbacks of venipuncture, the volume of blood that can be safely obtained, and the patient's preferred manner of getting the sample. Simulated skill training is a teaching strategy that aims to provide students with early education, enhance their confidence and skill development, and maximize process success while minimizing obstacles. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 19-23